Dealing with conflict and confrontation : how to keep your cool,stand your ground, and reach a positive solution (Careertrack, 2008)
this audio program shows hoew to learn psychological sound techniques proven to work on a varierty of conflicts. even in situations charged with potentially destructive behaviour, such as temper tantrums,tensions,anxiety and fear, one-upmanship, and flat-out lying.